Dari Keramat ke Sedekah: Living Hadith dan Perubahan Makna Tradisi Manganan - Nurjanah, Zumrotus Sholikatun; Mubarak, Alfoun Fajar; Amrulloh, Amrulloh (Jurnal Riset Agama, 2025)
Islam entered Indonesia when the people already had various traditions and cultures influenced by Hindu-Buddhist religions. One of these traditions is 'manganan', which is an almsgiving of the earth done by gathering and eating together. This research aims to explain the manganan tradition in Kapu Village, Merakurak Subdistrict, Tuban Regency through a living hadith approach. The method used is qualitative with field studies through interviews. This research uses the living hadith approach by integrating phenomenological theory to analyze the data. The results showed that there was an acculturation process from Hindu-Buddhist belief in the sacredness of the place, to an almsgiving event based on the teachings of the Prophet (PBUH), which is believed to bring good rewards in the future. This activity is also accompanied by Islamic activities such as khataman al-Qur'an, friendship and prayer together. This research concludes that the manganan tradition reflects the integration of Islamic values into local culture. The recommendation of this research is the need to preserve the manganan tradition while maintaining Islamic values so that it can become a forum for strengthening the cultural and spiritual identity of the community.